2020
DOI: 10.21037/atm.2020.01.38
|View full text |Cite
|
Sign up to set email alerts
|

Association between lipoprotein(a) concentration and the risk of stroke in the Chinese Han population: a retrospective case-control study

Abstract: Background: Lipoprotein(a) [Lp(a)] is a risk factor of coronary heart disease, however, its effects on stroke are less well-defined.Methods: We performed a single-center, retrospective case-control study in 1,953 and 196 ischemic stroke and hemorrhagic stroke in-hospital patients, respectively. Controls were healthy individuals that were matched for sex and age (±5 years) for the ischemic (1:1 ratio) and hemorrhagic (1:2 ratio) stroke. Lp(a) concentration was measured using the latex agglutination turbidimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, stroke was an important cause of death and disability at present. The prevalence rate continues to increased, and the affected population has shown a younger trend (Fu et al, 2020). Therefore, the prevention and treatment of stroke was a very serious problem in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, stroke was an important cause of death and disability at present. The prevalence rate continues to increased, and the affected population has shown a younger trend (Fu et al, 2020). Therefore, the prevention and treatment of stroke was a very serious problem in China.…”
Section: Introductionmentioning
confidence: 99%
“… Christopher et al, 1996 37 Asian Case–control study HB 50/50 27 ± 5 27 ± 5 Age, sex and socioeconomic status ELISA NA NA NA 5 6. Fu et al, 2020 38 Asian Case–control study HB 1953/1953 62.3 ± 11.8 59.9 ± 11.1 Age and sex Latex agglutination turbidimetric method 23.2 mg/dl NA NA 7 7. Dhamija et al, 2009 39 Asian Case–control study HB 66/72 54.43 ± 13 54.4 ± 13 Age and sex Immunoturbidimetric immunoassay ≤ 30 mg/dl Within 12 h NA 6 8.…”
Section: Resultsmentioning
confidence: 99%
“… Author name and year Ethnicity Study design Sample size (ICH/control) ICH age, years Control age, years Source of control Matching criteria LPA assay method LPA cut -off value LPA assay timepoint Follow up duration NOS quality score 1. Fu et al, 2020 38 Asian Case–control study 196/392 57.9 ± 13.7 57.9 ± 13.7 HB Age and sex Latex agglutination turbidimetric method 23.2 mg/dl NA NA 7 2. Sun et al, 2003 45 Asian Case–control study 499/1817 58.2 ± 9.7 59.6 ± 8.5 PB NA ELISA Within 6 weeks NA NA 7 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gudbjartsson DF and colleagues found that the odds ratio of 1.03 (95%CI: 1.00–1.07) for stroke for a 50 nmol/L increase in Lp(a) lost significance when KIV-2 repeats were used (OR: 1.01; 95%CI: 0.98–1.04) [ 27 ]. A recent retrospective case-control study indicated that elevated Lp(a) was significantly associated with increased ischemic stroke risk (OR = 2.03, 2.36, and 2.03 for quartiles 2, 3 and 4, respectively, vs. quartile 1) in Han Chinese individuals, especially among men and younger patients [ 31 ]. Some of the factors may have contributed to the differential findings among the present study and previous studies.…”
Section: Discussionmentioning
confidence: 99%